Productivity of kayu putih (Melaleuca leucadendron LINN) tree plantation managed in non-timber forest production systems in Java, Indonesia - , Budiadi ([Yogyakarta] : Fakultas Kehutanan UGM, 2003)
KaYIl plllih oil. extracted from. the kaYIl plllih tree (Melalellca lellcadendron), is an important non-timber forest product (NTFP) in Indonesia. We compared productivity of kaYIl plllih tree plantations among three different sites in East. Central. and West Java, Indonesia. Leaf-twig, and branch production per tree differed significantly among the three sites. Tree biomass production was highest at the site in West Java practicing tIImpang.flIri (a form of shifting cultivation) of kaYIl plllih with rice (Ory